EFFECT OF DIFFERENT LEVELS OF SOLUBLE FERTILIZERS ON NUTRIENT UPTAKE IN SOLANUM MELONGENA L. - A. ANBURANI, K. MUTHUMANICKAM, (Journal of Phytology, 2018)
Field investigation was carried out to study the influence of quality parameters and nutrient uptake of brinjal hybrids due to application of various levels of water soluble fertilizer. Foliar spray of NPK (19:19:19) at 0.5 per cent and 1% along with 100 and 75% recommended dose of NPK (200:150:100 kg ha-1) with 5 and 7 sprays, each starting from 30 DAT at 10 d interval, formed twenty treatments in two hybrids. Results showed that among the two different concentrations of foliar applied nutrients, 7 sprays of 1% NPK (19:19:19) along with 100 per cent recommended dose of fertilizer (200:150:100 kg ha-1) recorded the ascorbic acid content, total soluble solids (TSS) and total phenol content. Uptake of major nutrients was found to be the highest due to foliar application of 1 per cent water soluble fertilizer (7 sprays) along with 100 per cent recommended dose of fertilizer.